Eskatologi sebagai Sumber Pengharapan dan Penghiburan - Alfons Seran; Ronaldus Jonas Gea; Hildegardis Dwinag Angelita Lahagu; Maria Degli Angeli Fau; Imelda Iyun Kristina Nazara; Rosilia Buulolo (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study examines the meaning of eschatology in the teachings of the Catholic Church as a source of hope and comfort for the faithful. The eschatological meaning of comfort and hope is rooted in the belief that human life is not completed in limitations, suffering, and death at this time, but leads to the fulfillment of God's promise of life with Him. This research uses a qualitative method through literature study by analyzing church documents, theological thoughts and execes from books and articles to compile and present the topic of this research. The results show that the principle of eschatology is rooted in belief in the resurrection of Jesus Christ, and that it affirms the promise of eternal life and provides comfort and hope over suffering and death. The teachings of death, judgment, and eternal life are the basis of hope as well as comfort for the people in facing the various crises of life. In addition, eschatology is also relevant in today's life because it encourages people to live in love, justice, and moral responsibility as a manifestation of faith.